Strategi Komunikasi Krisis Kebijakan Pembelajaran Jarak Jauh melalui Media Sosial - Maulida, Rizkiya (Jurnal Riset Komunikasi (JURKOM), 2023)
Tthis article aimed to understand the crisis communication message from the Minsistry of Education of Republic Indonesia in handling the polemic due to the Online Learning Policy. The method used in this research is qualitative content analysis where the object of the analysis is the content of Nadeim Makarim’s Instagram account that related with the Online Learning policy during August-November 2020 period. The finding of this research will be analyzed with rhetoric perspective. The result of this research showed that the ethos that related with the source of the message has the most emphasize on the crisis communication message of Kemendikbud. In addition, Kemendikbud also implemented some narration to create a union feeling between the organization and stakeholders. Further research is needed to learn more about Kemendikbud’s public communication in handling another crisis.